Sensitifitas Multi-Atribute Decision Making Group dalam Pengambilan Keputusan pada Kasus Scoring Wilayah di Riau - Mustakim Mustakim (UIN Sultan Syarif Kasim Riau, 2015)
Education becomes a develop the potential of human resources in an area. Various the award will be given to areas that have the best potential related for education. The determination and scoring by relevant agencies to seek the best alternative from a set of alternatives. The concept of the group Multi-attribute Decision Making (MADM) applied in decision making method Simple Aditive Weighting (SAW), Weighting Product (WP), Tecnique for Order Preference by Similarity to Ideal Solution (TOPSIS) and the method of paired comparisons Analytic Hierarchy Process (AHP). A decision that produced a scoring area was chosen based on the calculation and analysis methods used the results of each method and the results of the hybrid method. In this research, there are three alternatives chosen, namely the A11, A6 and A8 for each respective method and incorporation method. Decision makers set a hybrid method as the final results used a reference for decision making by the percentage values are respectively 17.64%, 14.39% and 13.08%.Keywords: Analytic Hierarchy Process, Multi-attribute Decision Making, Simple aditive weighting, Scoring, weighting Product